Adverse Effects of Pharmacologic Treatments of Major Depression in Older Adults. Issue 8 (29th May 2019) - Sobieraj, Diana M.; Martinez, Brandon K.; Hernandez, Adrian V.; Coleman, Craig I.; Ross, Joseph S.; Berg, Karina M.; Steffens, David C.; Baker, William L.
Abstract : OBJECTIVES: To assess adverse effects of pharmacologic antidepressants for treatment of major depressive disorder (MDD) in adults 65 years of age or older. DESIGN: Systematic review and meta‐analysis. SETTING: Specialist or generalist outpatient setting, rehabilitation facility, and nursing facilities. PARTICIPANTS: Persons 65 years and older with MDD. INTERVENTION: Selective serotonin reuptake inhibitors (SSRIs), serotonin norepinephrine reuptake inhibitors (SNRIs), bupropion, mirtazapine, trazodone, vilazodone, or vortioxetine compared with another antidepressant, placebo, or nonpharmacologic therapy. MEASUREMENTS: Adverse events, arrhythmias, cognitive impairment, falls, fractures, hospitalization, mortality, QTc prolongation, serious adverse events, and withdrawals due to adverse events. RESULTS: Nineteen randomized controlled trials and two observational studies were included. Most studies evaluated treatment of the acute phase (<12 wk) of MDD of moderate severity. SSRIs led to a statistically similar frequency of overall adverse events vs placebo (moderate strength of evidence [SOE]), but SNRIs caused more overall adverse events vs placebo (high SOE) during the acute treatment phase. Both SSRIs and SNRIs led to more study withdrawals due to adverse events vs placebo (SSRIs low SOE; SNRIs moderate SOE). Duloxetine led to a more falls vs placebo (moderate SOE) during 24 weeks of acute and continuation treatment of MDD. CONCLUSION: In patients 65 years of age or older with MDD, treatment of the acute phase of MDD with SNRIs, but not SSRIs, was associated with a statistically greater number of overall adverse events vs placebo. SSRIs and SNRIs led to a greater number of study withdrawals due to adverse events vs placebo. Duloxetine increased the risk of falls that as an outcome was underreported in the literature. Few studies examined head‐to‐head comparisons, most trials were not powered to evaluate adverse events, and results of observational studies may be confounded. Comparative long‐term studies reporting specific adverse events are needed to inform clinical decision making regarding choice of antidepressants in this population. J Am Geriatr Soc 67:1571–1581, 2019 Abstract : See related editorial by Lenze and Ajam Oughli